2020
DOI: 10.3390/ph13060130
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Kinin Receptors in Human Wet and Dry Age-Related Macular Degeneration Retinae

Abstract: Kinins are vasoactive peptides and mediators of inflammation, which signal through two G protein-coupled receptors, B1 and B2 receptors (B1R, B2R). Recent pre-clinical findings suggest a primary role for B1R in a rat model of wet age-related macular degeneration (AMD). The aim of the present study was to investigate whether kinin receptors are differentially expressed in human wet and dry AMD retinae. The cellular distribution of B1R and B2R was examined by immunofluorescence and in situ hybridization in post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 70 publications
1
6
0
Order By: Relevance
“…Consistently with the roles of kinin receptors in both inflammation and neovascularization, we showed that most upregulated inflammatory mediators were blocked by B1R inhibition in DR and AMD [58][59][60]. B1R was shown to be expressed on Müller cells and astrocytes in these retinal pathologies in rat and post-mortem human retina [58,59,93], and on microglia in post-mortem human wet AMD retina [93]. Macroglia play a primary role in vascular function and neuronal integrity of the retina [145].…”
Section: Kallikrein-kinin System In Age-related Macular Degenerationsupporting
confidence: 77%
See 4 more Smart Citations
“…Consistently with the roles of kinin receptors in both inflammation and neovascularization, we showed that most upregulated inflammatory mediators were blocked by B1R inhibition in DR and AMD [58][59][60]. B1R was shown to be expressed on Müller cells and astrocytes in these retinal pathologies in rat and post-mortem human retina [58,59,93], and on microglia in post-mortem human wet AMD retina [93]. Macroglia play a primary role in vascular function and neuronal integrity of the retina [145].…”
Section: Kallikrein-kinin System In Age-related Macular Degenerationsupporting
confidence: 77%
“…In a mice model of CNV, B2R blockade with Icatibant had a limited effect, yet concomitant inhibition of B2R and kininase II had additive suppression of the CNV size [149]. We reported no significant modification of B2R mRNA and protein expression in human neovascular AMD retinae [93].…”
Section: Kallikrein-kinin System In Age-related Macular Degenerationmentioning
confidence: 60%
See 3 more Smart Citations